Tree planting campaign carried out in eight districts of the southern zone of Metropolitan Lima, Peru - Rivera, Alfredo (2025)
The objective of this study was to evaluate a tree planting campaign in the districts of Chorrillos, Lurin, Pachacamac, Punta Negra, San Juan de Miraflores, Santa Maria del Mar, Villa El Salvador and Villa Maria del Triunfo, located in the southern area of Metropolitan Lima, Peru. For this pur[1]pose, the survival rate of the tree individuals was assessed three months after being planted under the “Trees for Lima” program by the “Parks Service” (SERPAR). The goal was to determine the most suitable tree species for future afforestation projects according to their adaptability to different urban areas and response to maintenance efforts since initial establishment. The species with the highest number of planted individuals were “molle costeño” (Schinus terebinthifolia Raddi), “papelillo” (Koelreuteria paniculata Laxm.), “tipa” [Tipuana tipu (Benth.) Kuntze], “fresno” (Fraxinus americana L.) and “choloque” (Sapindus saponaria L.). The results indicated a survival rate of 10 455 trees out of a total of 10 590 planted, representing a 98.7 % survival rate after three months of evaluation.